Cascade hydroelectric scheme: River flow estimation for reservoir regulation improvement and flood-risk mitigation - Jidin R.; Othman A.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Budget control; Control systems; Estimation; Flood control; Floods; Flow measurement; Flow of water; Hydraulics; Hydroelectric power plants; Risk assessment; Risk management; Risk perception; Rivers; Stream flow; Travel time; Water levels; Flood risk management; Flood risks; Historical background; Hydroelectric reservoirs; Mathematical computation; River flow; River flow measurement; SCADA; Reservoirs (water)